2013
DOI: 10.1007/s00784-013-0985-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the parathyroid hormone 1 receptor in human periodontal ligament cells

Abstract: The findings further elucidate the characteristics of PTH action in dental tissues and widen the theoretical basis for the development of anabolic treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
1
9
0
1
Order By: Relevance
“…To demonstrate the effect of HMGB1 on early and late osteoblastic differentiation of hPDL cells, immunocytochemical staining on cover was performed using either a 1 : 50 (40 μ g/mL) working dilution of the primary antibody for ALP (rabbit anti-human; Quartett, Germany) or 1 : 25 (80 μ g/mL) for osteocalcin (rabbit anti-human; Biozol, Germany) in combination with a secondary fluorescence-labeled (Cy-3) antibody (1 : 100 (1.5 μ g/mL) working dilution; goat anti-rabbit; Invitrogen, Germany) and analyzed microscopically as reported previously [ 24 ]. Negative control were run by (i) omitting the primary antibody, (ii) omitting the primary and secondary antibody and using TBS/BSA instead, and (iii) by substituting the primary antibody by an unspecific IgG.…”
Section: Methodsmentioning
confidence: 99%
“…To demonstrate the effect of HMGB1 on early and late osteoblastic differentiation of hPDL cells, immunocytochemical staining on cover was performed using either a 1 : 50 (40 μ g/mL) working dilution of the primary antibody for ALP (rabbit anti-human; Quartett, Germany) or 1 : 25 (80 μ g/mL) for osteocalcin (rabbit anti-human; Biozol, Germany) in combination with a secondary fluorescence-labeled (Cy-3) antibody (1 : 100 (1.5 μ g/mL) working dilution; goat anti-rabbit; Invitrogen, Germany) and analyzed microscopically as reported previously [ 24 ]. Negative control were run by (i) omitting the primary antibody, (ii) omitting the primary and secondary antibody and using TBS/BSA instead, and (iii) by substituting the primary antibody by an unspecific IgG.…”
Section: Methodsmentioning
confidence: 99%
“…PTH1R is recognized by both PTH‐ and PTH‐related peptide (PTHrP) . PTH1R is coupled to the Gsα/PKA and the Gq/PLC/PKC . Previous studies have suggested that the activation of renal 1,25(OH) 2 D synthesis by PTH is via activating PKA signalling pathway and the regulation of renal 1,25(OH) 2 D secretion is via activating PKC signalling pathway .…”
Section: Introductionmentioning
confidence: 99%
“…30,31 The latter have been reported to share osteoblast-like traits and respond accordingly to hormonal stimulation. 32,33 PDL cells were shown to express the PTH 1 receptor (1R) 29 and respond to anabolic doses of PTH with changes of many crucial cell functions including proliferation, differentiation, apoptosis, and the production of key molecules of bone remodeling. [15][16][17] These findings are in line with the data obtained here in the monoculture experiments regarding proliferation and differentiation and strengthen the view of PDL cells as important regulators of periodontal remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…To visualize the effect of Wnt10b on hPDL cell differentiation along the osteoblastic pathway, immunocytochemical staining was performed using either a 1:50 (40 mg/ml) working dilution of the primary Ab for ALP (rabbit anti-human; Quartett, Germany) or 1:25 (80 mg/ml) for osteocalcin (rabbit anti-human; Biozol, Germany) in combination with a secondary fluorescence-labeled (Cy-3) Ab (1:100 (1.5 mg/ml) working dilution; goat anti-rabbit; Invitrogen, Germany) and analyzed microscopically as reported previously. 29 Negative controls were run by (i) omitting the primary Ab, (ii) omitting the primary and secondary Ab and using TBS/BSA instead, and (iii) by substituting the primary Ab by an unspecific IgG. The same protocol was followed for detection of LRP5 in hPDL cells using a monoclonal rabbit anti-human Ab (Cell Signaling Technology Europe, The Netherlands) using a 1:100 (20 mg/ml) working dilution.…”
Section: Immunofluorescence Cytochemistrymentioning
confidence: 99%